Digital Literacy and Scientific Literacy of Science Teachers and Student Learning Styles in Science Learning - Pursitasari, Indarini Dwi; Permana, Irvan; Jaenudin, Dadang; Suriansyah, Muhammad Iqbal; Sumiati, Eneng Sri; Aqilah, Siti (Department of Science Education, Universitas Sultan Ageng Tirtayasa, 2025)
The study aimed to analyze the teachers' understanding of scientific literacy based on the PISA 2025 framework, teachers' digital skills, and student learning styles. The descriptive method used in this research. Data was collected by surveying and distributing questionnaires to 305 students and 20 science teachers at Bogor. The data was analyzed quantitatively through the provision of scores, and then the percentage was determined. The results showed that the average teacher's digital literacy was 73.5%, teachers' understanding of scientific literacy based on the PISA 2025 framework was 77.1%, and students had visual, auditory, read/writing, and kinesthetic learning styles. Thus, digital literacy and teachers' literacy understanding are in a good category. The study results are the basis for science teachers in compiling e-books for science learning by considering students' learning styles.